Mediasi Komitmen Organisasional dan Kepuasan Kerja Karyawan, Iklim Organisasi Dan Kinerja Karyawan - Agusthina Risambessy; Conchita Valentina Latupapua; Kevin Chandra; Felix Chandra (Universitas Medan Area, 2022)
An effective organization must be able to create a conducive organizational climate to achieve the expected performance goals. To achieve this requires good human resource management accompanied by attention to factors that are able to become a liaison for the achievement of employee performance in accordance with the goals set by the organization. Job satisfaction and organizational commitment have been widely tested as connecting factors between employee performance. This study aims to examine and analyze the mediating role of organizational com-mitment and job satisfaction on the effect of organizational climate on employee performance. This research uses explanatory research design which can explain the setting of the variables studied and the relationship between one variable and another. The sampling method used was saturated sampling with 30 employees as respondents. After the data is collected, it is processed and analyzed using SMARTPLS 3.0. The results of the study have proven that (1) organizational commitment mediates the relationship between organizational climate and employee perfor-mance; (2) Job satisfaction mediates the relationship between organizational climate and em-ployee performance.